Epidemiology of Pertussis in Individuals of All Ages Hospitalized With Respiratory Illness in South Africa, January 2013—December 2018. (2nd February 2021) - Wolter, Nicole; Cohen, Cheryl; Tempia, Stefano; Walaza, Sibongile; Moosa, Fahima; du Plessis, Mignon; McMorrow, Meredith L; Treurnicht, Florette K; Hellferscee, Orienka; Dawood, Halima; Variava, Ebrahim; von Gottberg, Anne
Abstract: Background: Policy recommendations on pertussis vaccination need to be guided by data, which are limited from low- and middle-income countries. We aimed to describe the epidemiology of pertussis in South Africa, a country with high human immunodeficiency virus (HIV) prevalence and routine pertussis vaccination for 6 decades including the acellular vaccine since 2009. Methods: Hospitalized patients of all ages were enrolled at 5 sentinel sites as part of a pneumonia surveillance program from January 2013 through December 2018. Nasopharyngeal specimens and induced sputum were tested by polymerase chain reaction (PCR) for Bordetella pertussis . In addition, demographic and clinical information were collected. Incidence rates were calculated for 2013–2016, and multivariable logistic regression performed to identify factors associated with pertussis. Results: Over the 6-year period 19 429 individuals were enrolled, of which 239 (1.2%) tested positive for B. pertussis . Detection rate was highest in infants aged <6 months (2.8%, 155/5524). Mean annual incidence was 17 cases per 100 000 population, with the highest incidence in children <1 year of age (228 per 100 000). Age-adjusted incidence was 65.9 per 100 000 in HIV-infected individuals compared to 8.5 per 100 000 in HIV-uninfected individuals (risk ratio 30.4, 95% confidence interval: 23.0–40.2). Ten individuals (4.2%) with pertussis died; of which 7 were infants aged <6 months and 3 were immunocompromised adults. Conclusions: Pertussis continues to be a significant cause of illness and hospitalization in South Africa, despite routine vaccination. The highest burden of disease and death occurred in infants; however, HIV-infected adults were also identified as an important group at risk of B. pertussis infection. Abstract : In South Africa the incidence of hospitalized pertussis was 17 per 100 000 in all ages. Incidence was highest in infants, with 70% (7/10) of deaths in this age group. Adults infected with human immunodeficiency virus (HIV) were additionally at increased risk of B. pertussis infection.